It's Not Like That at All: A Poststructuralist Case Study on Language Teacher Identity and Emotional Labor - Kocabas-Gedik, Pinar; Hart, Deniz Ortactepe (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
This longitudinal case study explored the language teacher identity construction of two novice native English-speaking teachers (NESTs) in an EFL context. Adopting a poststructuralist approach, Emily's and David's teacher identity construction were explored in relation to the emotional labor they expressed and experienced throughout their first year at a university in Turkey. Data were collected over a six-month period through weekly journal entries, semi-structured follow-up interviews and researchers' field notes. While Emily and David had similar experiences as novice NESTs in their institution, three factors made a difference in their trajectories: educational background, competence in the local language, and supportive discourses at work. These three factors led to different emotional labor in their lives, and this contributed to their investment and participation in communities of practice. Overall, this study presents the ways in which emotional labor is interwoven with notions of investment, burnout, communities of practice, and teacher identity at large.
Keywords: Burnout; emotional labor; language teacher identity; native English-speaking teachers (NESTs); ENGLISH TEACHERS; PROFESSIONAL IDENTITY; INVESTMENT; CONSTRUCTION; BELIEFS; SPEAKER; Education & Educational Research; Linguistics